The association between severity of dental caries and salivary immunoglobulins in asthmatic adult patients (Indian Journal of Forensic Medicine & Toxicology, 2020)
The salivary samples were collected adequately from 80 subjects distributed equally (40 asthmatic subjectsand 40 control subjects) of ages range between 20-60 years. This comparative survey was determining thecaries index(DMFT),Streptococcus mutans , Streptococcus sobrinus ,salivary IgA and IgE. So this studyhave shown highly significant difference P ? (0.01) found in effect of age on salivary IgA in control adultsubjects and non-significant difference (P > 0.05) displayed in influence of age on salivary IgA. So thiscomparative investigation have demonstrated that non-significant difference (P > 0.05) found in influenceof age on salivary IgE to both groups of study. However, the correlation between age and salivary IgE is aweak negative relationship.